53rd AIAA Aerospace Sciences Meeting 2015
DOI: 10.2514/6.2015-1241
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Actuated Flexible Plates for Adaptive Shock Control Bumps

Abstract: Adaptive shock control bumps (SCB) aim to retain the performance of static SCV and improve off-design performance caused by variations in shock position due to flowfield unsteadiness and changes in aircraft cruise conditions. An adaptive SCB requires the flexibility to deform and the stiffness to withstand the complex pressure field that is present on the upper surface of a transonic aircraft wing. This study uses a quasi-steady aerostructural solver to design adaptive SCB. Both flexible and actuated plates ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 13 publications
(15 reference statements)
0
16
0
Order By: Relevance
“…For comparison a shock in the clean working section oscillates 50 mm. 4 The shock position is defined as the main normal shock location, labelled in figure 5 is x≈ 60 mm. information on plate deformation has also been extracted from PIV images and provides the geometry of the plate for each PIV vector field.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For comparison a shock in the clean working section oscillates 50 mm. 4 The shock position is defined as the main normal shock location, labelled in figure 5 is x≈ 60 mm. information on plate deformation has also been extracted from PIV images and provides the geometry of the plate for each PIV vector field.…”
Section: Resultsmentioning
confidence: 99%
“…2,3 The original concept was envisaged as a thin sheet to be deformed by actuators positioned along the length. Recent optimisation studies 4 have been designed to evaluate the performance of adaptive SCB. it was found that the flexibility of the structure necessary to produce suitable bump heights also allows the aerodynamic pressure load to affect plate deformation.…”
Section: Introductionmentioning
confidence: 99%
“…Jinks et al [81] (2015) describe a passive concept as well as an additional actuated approach. For both concepts the authors performed simulations with coupled fluidstructure interaction (FSI) as well as wind tunnel measurements.…”
Section: Thin Flexible Platementioning
confidence: 99%
“…For the wind tunnel model, Jinks et al [81] use a 0.4 mm thin aluminum plate (Al 7075 T6) that reaches from 40 to 60% chord. Since the shock is located at about 50% chord it is almost in the middle of the flexible airfoil surface.…”
Section: Thin Flexible Platementioning
confidence: 99%
“…Recently, studies by Rhodes and Santer [25,26] showed numerically that morphing SCBs, which can be deployed through the actuation of a flexible membrane, are possible where designs have been generated that offer an optimum trade-off between structural, material, and aerodynamic constraints. Further, research from Jinks et al [27][28][29][30] demonstrated the efficacy of the morphing SCB experimentally and numerically in pre-buffet flows. A limitation of this technique is that under current materials technologies, the sharp geometries required for wedge-bumps (especially in 3D) are not feasible due to sharp corners, requiring large variations in Gaussian curvature over short distances, as well as the additional actuation required.…”
Section: Introductionmentioning
confidence: 98%